Measuring Proximity Between Newspapers and Political Parties: The Sentiment Political Compass. Issue 3 (27th November 2019) - Falck, Fabian; Marstaller, Julian; Stoehr, Niklas; Maucher, Sören; Ren, Jeana; Thalhammer, Andreas; Rettinger, Achim; Studer, Rudi
Abstract : The proximity between newspapers and political parties is strongly subjective and difficult to measure. Yet, political tendencies of newspapers can have a significant impact on voters' opinion‐forming and ought to be known by the public in a transparent and timely manner. This article introduces the Sentiment Political Compass ( SPC ), a data‐driven framework for analyzing political bias of newspapers toward political parties. Using the SPC, newspapers are embedded in a two‐dimensional space (left‐leaning vs. right‐leaning, libertarian vs. autocratic). To assess the informative value of our framework, we crawled a data set consisting of 180, 000 newspaper articles from twenty‐five newspapers during the German Federal Elections over a time period of 18 months and extracted 740, 000 political entities enriched with their contextual sentiment. We analyze this dataset on the party‐ and politician‐level as well as considering the temporal dimension and draw insights about the relationship between newspapers and political parties. We provide the data set and our code open‐source at www.politicalcompass.de to encourage the application of the SPC to other political landscapes. 摘要: 报刊和政党之间的亲近程度是极具主观性且难以衡量的。尽管如此，报刊的政治倾向能对选民的意见形成产生显著影响，因此应该以一种透明且及时的方式被公众所熟知。本文引入"情感政治倾向测试"(SPS), 一项由数据驱动，用于分析报刊对政党所持的政治偏见的框架。通过使用SPS，报刊被置于一个二维空间（左倾与右倾，自由与专制)。为评估该框架的信息值，我们花费 18 个月的时间对一个数据集进行了搜索引擎爬行，该数据集由德国联邦选举期间 25 家报社发行的 180000 篇报刊文章组成，我们从中提取了 740000 个富含文本情感的政治实体。我们从党派和政客的层面分析该数据集，同时考量时间维度，并对报刊和政党之间的关系提炼出见解。我们在网站 www.politicalcompass.de 上提供了该数据集和代码开放源，以期鼓励 SPC 被应用于其他政治格局。 Resumen: La proximidad entre periódicos y partidos políticos es fuertemente subjetiva y difícil de medir. Sin embargo, las tendencias políticas de los periódicos pueden tener un impacto significativo en la formación de opinión de los votantes y deben ser conocidas por el público de manera transparente y oportuna. Este artículo presenta el Sentiment Political Compass (SPC), un marco basado en datos para analizar el sesgo político de los periódicos hacia los partidos políticos. Usando el SPC, los periódicos se incrustan en un espacio bidimensional (inclinado a la izquierda versus inclinado a la derecha, libertario versus autocrático). Para evaluar el valor informativo de nuestro marco, rastreamos un conjunto de datos que constaba de 180, 000 artículos periodísticos de 25 periódicos durante las elecciones federales alemanas durante un período de tiempo de 18 meses y extrajimos 740, 000 entidades políticas enriquecidas con su sentimiento contextual. Analizamos este conjunto de datos a nivel de partido y nivel político, así como teniendo en cuenta la dimensión temporal, y extraemos información sobre la relación entre los periódicos y los partidos políticos. Proporcionamos el conjunto de datos y nuestro código abierto en www.politicalcompass.de para alentar la aplicación del SPC a otros paisajes políticos.